Analysis Influence Dynamics Request to Sustainability Mobile Legends Jockey Business in the E-sports Industry - Aghiesna, Putri Isyam (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Study This aiming For analyze potential business jockey Mobile Legends as sector sustainable business in esports industry , with focus on dynamics request service said . Along with increasing popularity Mobile Legends among players and development esports ecosystem , services jockey has be one of a business that is of interest to players who want to climb the ranks in a way fast . This study use approach quantitative through survey questionnaire For identify factors that influence request to service jockey , including level competition in games , price services , and engagement player in the game. Research results show that request to service jockey driven by the height competition at a higher level of play height and needs player For increase ranking they with fast . Findings This indicates that business jockey own potential For develop become sector sustainable business in esports industry , during e-sports trends and competitions in Mobile Legends Keep going increased . Research This give contribution to literature about market dynamics in esports industry and potential business new emerging in competitive gaming ecosystem .